Variegation in the Number of Islets of Langerhans in the Pancreas of Rats Fed on Sodium Cyclamate - Kundi, Hina; Waseem, Naureen; Qamar, Abdullah; Bilal, Ruqqia; Qureshi, Saima; Yousaf, Maria (Pakistan Armed Forces Medical Journal, 2022)
Objective: To observe the effects of an artificial sweetener (sodium cyclamate) on a rat’s pancreas and glucose levels. Study Design: Laboratory-based experimental study. Place and Duration of Study: Army Medical College Rawalpindi, in association with the National Institute of Health, Islamabad, Pakistan from Jun 2014 to Jan 2015. Methodology: Forty Sprague Dawley rats (male and female housed separately to avoid mating and pregnancy) were involved in the experiment. Twenty rats in each control and experimental group. C served as control and E for the experimental group. A normal laboratory diet was fed to control Group-C for two months, whereas through an oral gavage needle, artificial sweetener 60mg/kg/day (sodium cyclamate) was fed to experimental animals for two months. During the two months after twelve-hour fasting, rats’ blood glucose level was recorded weekly. At the commencement and completion of these two months, the weight of the animals was noted. Results: Fasting blood sugars of experimental group was found to be statistically significant from week 3 to 9 with p-values of 0.034, <0.001, <0.001, 0.002, 0.001, <0.001, <0.001 respectively. Number of islets of Langerhans was significantly higher 13.70 ± 1.87μm in experimental group compared with control group with the p-value of <0.001. Conclusion: Sodium cyclamate not only affected the glucose metabolism but also disturbed the normal histology of the endocrine pancreas.